Does visual information influence infants’ movement to music? - Morgan, Gin (2013)
Humans are often exposed to music beginning at birth (or even before birth), yet the study of the development of musical abilities during infancy has only recently gained momentum. The goals of the present study were to determine whether young infants (ages four to seven months) spontaneously moved rhythmically in the presence of music, and whether the presence of visual information in addition to music would increase or decrease infants’ movement. While nearly all infants moved in the presence of music, very few infants demonstrated rhythmic movement. Results revealed that, when visual information was present, and particularly when infants appeared to show focused attention toward the visual information, infants moved less than when only auditory information was present. The latter result is in agreement with most studies of sensory dominance in adults in which visual stimuli are dominant over auditory stimuli.